1984
DOI: 10.1530/acta.0.1070275
|View full text |Cite
|
Sign up to set email alerts
|

Endocrinological effects of single daily ketoconazole administration in male beagle dogs

Abstract: Abstract. Some endocrinological effects of single daily oral administration of 150 mg ketoconazole for 15 days were investigated in 4 male beagle dogs. Plasma testosterone fell markedly within 3–4 h and then progressively returned to control concentrations by 10 h after drug administration. On the other hand, plasma 17α-hydroxyprogesterone, progesterone and 17α,20α-dihydroxyprogesterone increased within 3–10 h before returning to basal values after 24 h. Plasma LH did not rise significantly though some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
22
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 0 publications
2
22
0
Order By: Relevance
“…Although this points the way to the development of an orally administered, rapid onset means of male contraception, it is not proposed that ketoconazole be pursued further for this purpose. The suppressive effects on circulating levels of testosterone noted in the present and other experiments in dogs [42], which are borne out by reports in men [43][44][45] and which are mediated through effects on cytochrome P-450 [46], would be expected to result in symptoms of testosterone withdrawal including loss of potentia and libido, hot flashes, and gynecomastia. In addition, the reported idiosyncratic hepatotoxicity in man [47] would militate against the use of ketoconazole as a contraceptive.…”
Section: Discussionsupporting
confidence: 54%
“…Although this points the way to the development of an orally administered, rapid onset means of male contraception, it is not proposed that ketoconazole be pursued further for this purpose. The suppressive effects on circulating levels of testosterone noted in the present and other experiments in dogs [42], which are borne out by reports in men [43][44][45] and which are mediated through effects on cytochrome P-450 [46], would be expected to result in symptoms of testosterone withdrawal including loss of potentia and libido, hot flashes, and gynecomastia. In addition, the reported idiosyncratic hepatotoxicity in man [47] would militate against the use of ketoconazole as a contraceptive.…”
Section: Discussionsupporting
confidence: 54%
“…Nonetheless, gynaecomastia has been reported in a few patients treated with high-dose ketoconazole therapy (De Felice et al 1981) suggesting that the drug might interfere with other cytochrome P-450-dependent steps in the steroidogenic pathway. Fur¬ ther investigations have in fact confirmed that short-term administration of ketoconazole pro¬ vokes a dose-dependent but transient block in the production of testosterone (Pont et al 1982a;Santen et al 1983;Schürmeyer & Nieschlag 1984;De Coster et al 1984). Along the same lines it has been demonstrated that ketoconazole and several related compounds block testosterone secretion by rat (Pont et al 1982a) and mouse (Schürmeyer & Nieschlag 1984) Leydig cells in vitro.…”
mentioning
confidence: 93%
“…In addition, glucocorticoid antagonist activity due to occupancy of glucocorticoid receptors has been shown in cultured hepatoma cells (8). Low dose ketoconazole (200 mg) administration to normal men caused a selective and fully reversible block of the Ci7_2o lyase (9), explaining the drug's potent inhibitory effect on testosterone production (9)(10)(11)(12)(13). Clinical data concerning adrenal effects also are available.…”
mentioning
confidence: 99%